Implementasi Digital Marketing Dalam Pemasaran Pariwisata Hutan Kota “Punti Kayu” Di Palembang - Agus Yusrizal Bakri; Loren Diaz Lintang; Juwita Puja Anggraini; Tata Sutabri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Tourism is now a sector that is experiencing rapid growth supported by developments in information and communication technology. One of the potential tourism destinations in Palembang is the